Anglesite and silver recovery from jarosite residues through roasting and sulfidization-flotation in zinc hydrometallurgy - Han, Haisheng; Sun, Wei; Hu, Yuehua; Jia, Baoliang; Tang, Honghu (Journal of hazardous materials, 2014)
•Jarosite precipitate hindered the recovery of valuable minerals.•Under 600–700°C, jarosite decomposed and released the encapsulated valuable minerals.•The bared valuable minerals were easily collected by flotation process.•The new process was promising for dealing with jarosite residues. Hazardous jarosite residues contain abundant valuable minerals that are difficult to be recovered by traditional flotation process. This study presents a new route, roasting combined with sulfidization-flotation, for the recovery of anglesite and silver from jarosite residues of zinc hydrometallurgy. Surface appearance and elemental distribution of jarosite residues was examined by scanning electron microscopy and energy dispersive X-ray spectrometry analysis, respectively. Decomposition and transformation mechanisms of jarosite residues were illustrated by differential thermal analysis. Results showed that after roasting combined with flotation, the grade and recovery of lead were 43.89% and 66.86%, respectively, and those of silver were 1.3kg/t and 81.60%, respectively. At 600–700°C, jarosite was decomposed to release encapsulated valuable minerals such as anglesite (PbSO4) and silver mineral; silver jarosite decomposed into silver sulfate (Ag2SO4); and zinc ferrite (ZnO·Fe2O3) decomposed into zinc sulfate (ZnSO4) and hematite (Fe2O3). Bared anglesite and silver minerals were modified by sodium sulfide and easily collected by flotation collectors. This study demonstrates that the combination of roasting and sulfidization-flotation provides a promising process for the recovery of zinc, lead, and silver from jarosite residues of zinc hydrometallurgy.